Benign‐by‐Design Solventless Mechanochemical Synthesis of Three‐, Two‐, and One‐Dimensional Hybrid Perovskites. (28th October 2016) - Jodlowski, Alexander D.; Yépez, Alfonso; Luque, Rafael; Camacho, Luis; de Miguel, Gustavo
Abstract: Organic–inorganic hybrid perovskites have attracted significant attention owing to their extraordinary optoelectronic properties with applications in the fields of solar energy, lighting, photodetectors, and lasers. The rational design of these hybrid materials is a key factor in the optimization of their performance in perovskite‐based devices. Herein, a mechanochemical approach is proposed as a highly efficient, simple, and reproducible method for the preparation of four types of hybrid perovskites, which were obtained in large amounts as polycrystalline powders with high purity and excellent optoelectronics properties. Two archetypal three‐dimensional (3D) perovskites (MAPbI3 and FAPbI3 ) were synthesized, together with a bidimensional (2D) perovskite (Gua2 PbI4 ) and a "double‐chain" one‐dimensional (1D) perovskite (GuaPbI3 ), whose structure was elucidated by X‐ray diffraction.